Evaluation of Non Alcoholic Fatty Liver Disease in T2dm Patients and Abnormalities in Liver Enzymes, Lipid Pro?le in Patients with Fatty Liver in Comparison with Patients without Fatty Liver - Sudheer Ranganath; Dr Basawaraj (Asian Journal of Medical Radiological Research, 2021)
Introduction: The non-alcoholic fatty liver disease (NAFLD), seen in patients with T2DM. Recently, it has been documented that NAFLD prevalence has been increasing in paraller with increasing obesity and T2DM. NAFLD, the most common hepatic disease. This study aimed   to determine the prevalence of NAFLD in T2DM patients, diagnosed by liver ultrasound and to see the differences in hepatic enzymes, lipid parameters between patients with NAFLD and individuals without NAFLD. Subjects and Methods: This study conducted at Department of Radiodiagnostics, BGS Global Institute of Medical Sciences, Kengeri, Bengaluru, Karnataka. A total of 200 subjects were involved in this study, among them 100 were T2DM patients as cases and 100 healthy subjects as controls. The physical and clinical examination was done for all the subjects. The patients were categorized into 2 groups, based on the liver size and echo texture. Group I include T2DM patients with NAFLD and group II include T2DM patients without NAFLD. Under aseptic condition, fasting venous blood samples were collected from all the subjects, centrifuged to obtain serum. The obtained serum was used for the estimation of fasting blood sugar (FBS), post-prandial blood sugar (PPBS), aspartate transaminase, alanine transaminase, alkaline phosphatase, gamma-glutamyl transferase and lipid profile. Fatty liver was diagnosed   on USG based on echogenicity and liver size. The liver examination was carried by using Samsung Medison UGEO and GE voluson P8 with curvilinear array transducers starting with 3-7 MHz. The size of the liver was measured in midclaviclar line longitudinally and <14 cm was taken as controls and >14 was considered as hepatomegaly. Results: In this study, significantly increased age was observed in T2M patients with NAFLD and without NAFLD compared to healthy controls. The liver size, aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT) and serum cholesterol, triglycerides and LDL-cholesterol were increased significantly in T2DM patients compared to controls. In subgroup analysis, in group I, liver size, AST, ALT, ALP, GGT, serum cholesterol and triglycerides were significantly high when compared to group II patients. Conclusion: In the present study, NAFLD prevalence is 65% among T2DM patients. Dyslipidemia and increased heaptic enzymes such as AST, ALT, ALP and GGT are seen more frequently in group I than group II. Early detection and optimum control of diabetes mellitus is important to reduce the effect of diabetes on liver.